2021
DOI: 10.3390/v13081562
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Characterization and Pathogenicity of a Novel Porcine Epidemic Diarrhea Virus (PEDV) with a Naturally Occurring Truncated ORF3 Gene Coinfected with PEDVs Possessing an Intact ORF3 Gene in Piglets

Abstract: Coinfection caused by various genotypes of porcine epidemic diarrhea virus (PEDV) is a new disease situation. We previously reported the coexistence of PEDV strains containing different ORF3 genotypes in China. In this study, the PEDV strains 17GXCZ-1ORF3d and 17GXCZ-1ORF3c were isolated and plaque-purified from the same piglet, which had a natural large deletion at the 172–554 bp position of the ORF3 gene or possessed a complete ORF3 gene, respectively. Meanwhile, 17GXCZ-1ORF3d had >99% nt identity with 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
(66 reference statements)
1
12
0
Order By: Relevance
“…Nevertheless, the truncated ORF3 HN2021 strain belonging to G2 genotype appeared to be highly virulent to suckling piglets. Similar results emerged in the 17GXCZ-1ORF3d strain belonging to G2 genotype, which has a naturally truncated ORF3 gene containing a continuous 382 nucleotide deletions from 172–554 nt and has been verified as a virulent strain causing severe diarrhea and high mortality in suckling piglets [ 18 ]. The genotype of PEDV is closely related to pathogenicity and immune protection [ 38 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Nevertheless, the truncated ORF3 HN2021 strain belonging to G2 genotype appeared to be highly virulent to suckling piglets. Similar results emerged in the 17GXCZ-1ORF3d strain belonging to G2 genotype, which has a naturally truncated ORF3 gene containing a continuous 382 nucleotide deletions from 172–554 nt and has been verified as a virulent strain causing severe diarrhea and high mortality in suckling piglets [ 18 ]. The genotype of PEDV is closely related to pathogenicity and immune protection [ 38 ].…”
Section: Discussionsupporting
confidence: 62%
“…The cDNA was screened by RT-qPCR (quantitative real-time RT-PCR), the primers targeting the PEDV M gene were designed ( Table S1 ), and RT-qPCR was conducted by using the Premix Ex Taq™ kit (TaKaRa) on a real-time thermocycler (CFX96™ Optics Module; BIO-RAD; California, CA, USA). For ORF3 amplification, the primers against ORF3 gene ( Table S1 ) were used [ 18 ]. Then, a total of 20 pairs of primers were designed to amplify the complete genome of the PEDV strain by conventional RT-PCR ( Table S1 ), and the positive cDNA was selected and amplified for complete genome.…”
Section: Methodsmentioning
confidence: 99%
“…The first reverse genetics system of SARS-CoV-2 assembled in yeast using a YAC-based vector (pVC604) remained stable in yeast; however, their stability in E. coli was not evaluated (Thi Nhu Thao et al, 2020) In a previous study, CRISPR/Cas9 technology was applied to edit the PEDV genome with a BAC-based infectious cDNA clone (Peng et al, 2020), which was demonstrated to be a simple and rapid method. Deletions within ORF3 were detected in vaccine strains and many field PEDV strains (Cui et al, 2020;Lu et al, 2020bLu et al, , 2021, suggesting that ORF3 may be non-essential for viral replication. Using reverse genetics systems, ORF3 was demonstrated to be not critical for PEDV replication and can be successfully replaced with reporter genes (Beall et al, 2016;Kaewborisuth et al, 2018;Peng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…PEDV has an enveloped single-stranded RNA genome that is approximately 28 kilobases (kb) long with a 5′ untranslated UTR region as well as a 3′ UTR [ 8 ]. The PEDV genome encodes two replicase polyproteins (ORFs 1a and 1b), four structural proteins (spike S, envelope E, membrane M and nucleocapsid N) and one accessory protein encoded by ORF3 [ 13 , 14 ]. According to the difference of the S gene, PEDV can be divided into two types: G1 and G2 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%